A Multidimensional Approach to the Gender Gap in Poverty: An Application for Turkey. Issue 2 (3rd April 2022) - Tekgüç, Hasan; Akbulut, Bengi
Abstract : Conventional poverty measures have long been criticized as a poor gauge of quality of life. Household-level income or expenditure data used in these measures are silent on intrahousehold inequalities and capture means to an end rather than outcomes and opportunities individuals face. This article constructs a multidimensional poverty index (MPI) to address these problems. It calculates multidimensional poverty for Turkey in four equally weighted dimensions: education, health, employment, and household living conditions. The study introduces employment as a distinct dimension of well-being, which is especially pertinent for the gender gap in poverty in the Turkish context. It finds a significant (30–34 percent) gender poverty gap, which is gradually narrowing over time. However, there is very little convergence between regions. Finally, results show households with multidimensionally poor women and non-poor men as the most common sub-group and an increase in the share of households with no poor members. HIGHLIGHTS The study evaluates the multidimensional poverty of individuals to analyze gender gaps. Employment proxies for ignored functionings like self-respect and social inclusion. Gender poverty gap was between 30 and 34 percent during 2006–15. Gender poverty gap is only closing for the youngest cohorts. Within-household poverty disparities are high and stable during 2006–15.